What effect does siderite crystal growth have on chlorides and potential information within the corrosion products of archaeological iron artefacts? - Ruben With (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
In anoxic, carbonated and slightly acidic burial environments, the growth of siderite crystals on archaeological iron has been attributed a passivating effect on the corrosion process. By creating a simplified, though similar environment (optimized for siderite growth), the aim of this project was to observe how the growth of siderite crystals within the corrosion crust of archaeological iron objects would affect both the corrosion crust and its chloride content.